Factors that contribute to a NANDA nursing diagnosis of risk for frail elderly syndrome - Maria da Graça Oliveira Crossetti; Michele Antunes; Beatriz Ferreira Waldman; Margarita Ana Rubin Unicovsky; Lucas Henrique de Rosso; Letice Dalla Lana (Universidade Federal do Rio Grande do Sul, 2018)
Abstract OBJECTIVE Identify the risk factors that contribute to a NANDA-I nursing diagnosis of risk for frail elderly system. METHOD Cross-sectional study with 395 elderly subjects, conducted from November 2010 to January 2013, in a university hospital in South of Brazil. Sociodemographic data were collected and levels of frailty were identified according to the Edmonton Frail Scale. RESULTS A total of 177 (44.81%) participants were classified as frail. There was a significant association between frailty and being female (p=0.031), nonwhite (p=0.008), having no romantic partner (p=0.014), no schooling (p=0.001), a monthly income lower than the minimum wage (p=0.034), and preexisting morbidities for respiratory diseases (p=0.003) as well as infectious and parasitic diseases (p=0.040). Diseases of the tracts genitourinary (p=0.035), respiratory (p=0.001) and blood (p=0.035) were the primary reasons for hospitalization. CONCLUSIÓN Los resultados contribuyen para el desarrollo e implementación del diagnóstico de enfermería en estudio en el ambiente hospitalario.